Investigation of dissolved salts on heat transfer for aluminum alloy 2024 during spray quenching. (25th August 2016) - Guo, Ruichao; Wu, Jianjun; Fan, He; Zhan, Xuepeng; Hui, Yu
Highlights: Four dissolved salts on spray quenching heat transfer are investigated. No film boiling regime is observed. Different changing trends are found at both nucleate and transition boiling regimes. The largest enhancement of heat transfer is shown at the concentration of 0.2 M for NaCl, CaCl2 and MgSO4 solutions, in contrast to 0.06 M for Na2 SO4 solution. Abstract: An experiment was performed to investigate the influence of four dissolved salts (NaCl, CaCl2, Na2 SO4 and MgSO4 ) on heat transfer. Concentration of all salts varied from 0.01 M to 0.4 M. And deionized water (DI water) was used as the solvent. The aluminum alloy 2024 thin sheets were heated to 495 °C and quenched by two spray nozzles with a constant range of volumetric flux. Time-temperature curves were smoothed by B-spline approximation with a smoothing parameter of 10 −4 . The results indicate that only MgSO4 solution increases both nucleate boiling and transition boiling heat flux. Solution of CaCl2 has the greatest influence on nucleate boiling heat transfer, followed by Na2 SO4 compared with the minimum influence of NaCl. These effects are attributed to the surface tension gradient, transition concentration and vapor pressure for different salts. The largest heat flux enhancement is observed at concentration of 0.2 M for solutions of NaCl, CaCl2 and MgSO4 in contrast to 0.06 M for Na2 SO4 .